IMPLEMENTASI PENGUATAN PROFIL MATA KULIAH KEWIRAUSAHAAN UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA PADA MAHASISWA ADMINISTRASI PENDIDIKAN UNIVERSITAS JAMBI - Dedi Aribowo; Firman Firman; Linardo Pratama (Jurnal Manajemen Pendidikan, 2025)
Objective: This study aimed to determine the implementation of strengthening the profile of the entrepreneurship course in fostering entrepreneurial interest among Educational Administration students at Jambi University. The research used a qualitative method with a case study approach, and data were collected through observation, interviews, and documentation. The participants included the coordinator of the entrepreneurship course, lecturers who taught the course, and students. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that the Semester Learning Plan (RPS) for the entrepreneurship course had been uniformly prepared by the university and regularly updated to remain relevant to the dynamics of the business world. Additionally, the learning methods applied in the Educational Administration Study Program were active and experience-based, particularly through project-based learning. Students’ responses indicated a positive tendency toward the entrepreneurship course, especially when the learning process was delivered in an engaging manner.